2009
DOI: 10.21608/eajbse.2009.16460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extrinsic incubation temperature on transstadial and transovarial transmission of Borrelia sp. in Ornithodoros (O.) savignyi and infectivity to vertebrate host.

Abstract: Effects of three extrinsic incubation (EI) temperatures on vector competence of Ornithodoros savignyi to Borrelia sp. isolated from a natural population of the tick in Egypt were investigated. The EI temperature influenced the efficiency of Borrelia sp. transmission by the female O. savignyi to hamsters. An EI temperature for 27 o C was optimum for successful transmission of Borrelia sp. where the highest infection rates (IRs) in hamsters occurred. Generally, the IRs in hamsters decreased by lowering the EI te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Generally, female ticks were more efficient than males and adults than immatures in transmitting borrelial infection as lower numbers of these life stages are required to produce similar or higher levels of infectivity to the rabbit fed upon by each species. The present results agree with those of previous investigators of other ixodids (Piesman & Sinsky, 1988) and argasid ticks (Shanbaky and Helmy 2000) Those authors found that the efficiency of transmitting Borrelia in ticks had increased by increasing the number of infected ticks per host animal, apparently the feeding of a larger number of infected ticks inoculates the host animal with a bigger number of spirochetes than the feeding of a smaller number. Lane et al, (1994) found that the plasma antibody titer of B. burgdorferi increased from 1.128 to 1.256 in mice exposed to feeding by one and two infected nymphs, respectively in I. pacicicus.…”
Section: Transmission Of Borrelial Infection To Rabbitssupporting
confidence: 93%
See 2 more Smart Citations
“…Generally, female ticks were more efficient than males and adults than immatures in transmitting borrelial infection as lower numbers of these life stages are required to produce similar or higher levels of infectivity to the rabbit fed upon by each species. The present results agree with those of previous investigators of other ixodids (Piesman & Sinsky, 1988) and argasid ticks (Shanbaky and Helmy 2000) Those authors found that the efficiency of transmitting Borrelia in ticks had increased by increasing the number of infected ticks per host animal, apparently the feeding of a larger number of infected ticks inoculates the host animal with a bigger number of spirochetes than the feeding of a smaller number. Lane et al, (1994) found that the plasma antibody titer of B. burgdorferi increased from 1.128 to 1.256 in mice exposed to feeding by one and two infected nymphs, respectively in I. pacicicus.…”
Section: Transmission Of Borrelial Infection To Rabbitssupporting
confidence: 93%
“…The observed higher percentages of borrelial infection in the laboratory than in nature might be attributed to the relatively optimum conditions of survival offered to the tick and pathogen in the laboratory versus the challenging and varied conditions in nature as environmental temperature, humidity, vertebrate hosts kinds, availability etc. which have been found to affect different physiological processes and interrelationships in both organisms (Schwan et al, 1995;Shanbaky et al, 2009;Wallace et al, 2019).…”
Section: Acquisition Of Borreliamentioning
confidence: 99%
See 1 more Smart Citation